2014
DOI: 10.1155/2014/832850
|View full text |Cite
|
Sign up to set email alerts
|

Nonactivated and Activated Biochar Derived from Bananas as Alternative Cathode Catalyst in Microbial Fuel Cells

Abstract: Nonactivated and activated biochars have been successfully prepared by bananas at different thermotreatment temperatures. The activated biochar generated at 900°C (Biochar-act900) exhibited improved oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) performances in alkaline media, in terms of the onset potential and generated current density. Rotating disk electron result shows that the average of 2.65 electrons per oxygen molecule was transferred during ORR of Biochar-act900. The highest powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…16 In brief, 5 g of chitin and 40 mL deionized water were placed in a commercial Teflon-lined autoclave with a capacity of 50 mL, and the autoclave was sealed and heated at 180 ºC for 12 h. The resulting hydrothermal carbonaceous solid was recovered and washed with ethanol and deionized water several times, dried in an oven at 60 ºC, and ground in an agate mortar. Subsequently, the carbonaceous solid was thermo treated at 750 ºC for 2 h (dwell time) at a heating rate of 5 ºC/min in a tube furnace under an inert atmosphere to obtain unactivated chitin-based carbon sheet (CS).…”
Section: Preparation Of Activated Carbon Sheet From Chitinmentioning
confidence: 99%
“…16 In brief, 5 g of chitin and 40 mL deionized water were placed in a commercial Teflon-lined autoclave with a capacity of 50 mL, and the autoclave was sealed and heated at 180 ºC for 12 h. The resulting hydrothermal carbonaceous solid was recovered and washed with ethanol and deionized water several times, dried in an oven at 60 ºC, and ground in an agate mortar. Subsequently, the carbonaceous solid was thermo treated at 750 ºC for 2 h (dwell time) at a heating rate of 5 ºC/min in a tube furnace under an inert atmosphere to obtain unactivated chitin-based carbon sheet (CS).…”
Section: Preparation Of Activated Carbon Sheet From Chitinmentioning
confidence: 99%
“…In an ongoing effort to identify potential cheaper alternatives, the use of various cathode catalysts (nonprecious metal) on carbon paper or cloth has been considered for MFCs. These include the use of nonactivated and activated biochars prepared from banana, 8 iron aminoantipyrine (Fe-AAPyr), 9 cobalt-aminoantipyrine (Co-AAPyr), 9 nickel aminoantipyrine (Ni-AAPyr), 9 manganese-aminoantipyrine (Mn-AAPyr), 9 manganese oxides with a cryptomelane-type octahedral molecular sieve, 10 flower-like cobalt(II,III) oxide (Co 3 O 4 ), 11 iron-based catalysts, 12 and platinum−iron−titanium dioxide (Pt−Fe/TiO 2 ). 13 The methods used in various studies for deposition of catalyst on a gas diffusion layer (GDL) include brush coating, 14 inkjet printing, 15 ultrasonic spray coating, 16 doctor blade coating, 17 and sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…N-doped carbon obtained at 900 °C with an intermediate N-content and surface area showed the best ORR catalytic property among the other catalysts prepared that was also higher than that of Pt/C with 3.86 electron transfer per oxygen molecule, suggesting the four-electron pathway during the ORR. Yuan et al reported the synthesis of N-doped carbon using the chemical activation of biochar obtained from the banana plant [ 151 ]. Moreover, a hydrothermal treatment followed by annealing under N 2 gas to plant moss (Weisiopsisanomala), a phylum of small and soft plants, commonly available plant species, could produce carbon nanoparticle-decorated N-doped porous carbon, which also served as a superior ORR catalyst in MFCs [ 152 ].…”
Section: Carbon-based Oxygen Reduction Reaction Catalystsmentioning
confidence: 99%